QAULAN-BASED COMMUNICATION IN ISLAMIC RELIGIOUS EDUCATION: THE ROLE OF MADRASAH LEADERSHIP AND INSTITUTIONAL CULTURE - Iwan Aprianto; Hairul Fauzi; M. Shoffa Saifillah Al Faruq; Makmur Harun (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to implement six Qur'an-based communication principles in Islamic Religious Education (PAI) learning at Madrasah Aliyah in Batanghari Regency, Jambi Province. Using a qualitative multi-site case study design, the research involved participants from each school principal and Islamic Education teacher with diverse accreditation (A, B, C). Data were collected through observation, interviews, and documentation, and analyzed using Miles, Huberman, and Saldaña's interactive model. Findings reveal that the three dimensions (madrasah leadership, institutional culture, and instructional practices work) synergistically to implement qaulan-based communication through integrity, harmony, and pedagogical effectiveness. Together, those created an integrative, humane, and transformative communication environment that strengthens students’ religious character and enhanced the quality of interactions within the madrasah. The implications of this study highlighted the importance of systematically integrating qaulan-based communication into educational policies, leadership practices, and classroom strategies to foster a humane and transformative learning environment.